A method to assess dermal absorption dynamics of chemical warfare agents: Finite doses of volatile compounds. - Lear, Koko; Simon, Laurent (Journal of Occupational & Environmental Hygiene)
Chemical warfare agents are absorbed into the body from various entry routes and may have detrimental effects on human health. As many chemical compounds in this group are lipophilic, the outer layer of the skin is at an elevated risk. This contribution explores the dynamics of skin penetration for risk assessment. A previously validated model was applied to describe how an agent is transported across the stratum corneum following dermal exposure to a finite dose of a chemical. A mathematical construct was implemented for estimating the time constants and the cumulative amount of permeant entering the bloodstream or being released into the environment. Empirical equations were selected to determine the ratio of the steady-state evaporation rate to the steady-state dermal absorption rate and the physicochemical properties of the chemical warfare agents. Wolfram Mathematica was employed to run the simulations. The results from the newly derived expressions for the time constants matched those directly obtained from the validated model. For example, sarin gas had steady-state evaporation to an absorption rate of 991.25, and a total fractional absorption and evaporation of 5.1% and 94.9%, respectively. Combined with occupational exposure limits, the findings can help researchers assess an individual's risk level and develop protection programs.